Upaya Fasilitasi Pajak Online Kelompok UMKM Cibinong, Kabupaten Bogor, Jawa Barat - Ekowati, Lia; Listiawati, Rodiana; Ratri S, Dini Ayuning; Redyanita, Hastuti; Mahatmyo, Atyanto (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2024)
The existence of the Cibinong District MSME forum, Bogor Regency, which can gather MSME players in the region is very meaningful. Business actors have a very basic problem regarding NPWP ownership and knowledge about NPWP is also still very minimal for MSMEs in the region. NPWP ownership is the basis for a business that wants to upgrade in its business. Community service which is a routine activity of the PNJ DIII Finance and Banking Study Program aims to help partners utilize their gadgets in making NPWP online. NPWP ownership is one of the requirements for entrepreneurs, both individuals and business entities, who want to apply for loans to banking and non-banking business institutions. The Ministry of Finance urges all levels of society to register as taxpayers and benefit from these efforts. This appeal is intended for people who have fulfilled the requirements in accordance with the provisions of tax legislation based on the self-assessment system in order to avoid tax sanctions. Therefore, the community service team provided assistance in making NPWP online. This training and mentoring was held at the Bogor Regency Bappedalitbang Building on July 11, 2023 with 30 training participants. The implementation of the training includes an explanation of the importance of NPWP and direct assistance in making NPWP online, accompanied and guided by the committee. It is expected that from this training activity, MSME players in Bogor District can directly have an NPWP for their business and this NPWP can be used properly.